Estudo das relações enunciativas do editorial da revista Graça Show da Fé da Igreja Internacional da Graça de Deus - Pereira, Taís (2008)
The neopentecostal religious discourse has been grown on Brazilian mass media circuit since 1970 s, accompanying impressive increase of the neopentecostal Christians on Brasil. One of these neopentecostal churches is called Igreja Internacional da Graça de Deus (IIGD). In such scenario, among neopentecostal churches, IIGD it is the greatest user of mass media resources. Those resources are used to disseminate own doctrine. IIGD has acquainted more hours on television media and offered more products with doctrinarian tone. Among its products, it can be registered a journal of national circulation, Revista Graça Show da Fé (RGSF). Through simple and hyperbolic language, RGSF performs a very persuasive discourse that results in not only many people adhered to IIGD but also it registers a distinctive performance of eight years of journal distribution. RGSF is a religious journal and its editorial is marked by unique elements by comparing it to a genre of editorial. In RGSF s editorial, the editor has preached, persuasively, his doctrine and commanded his readers, whose is called by him as Show da Fé sponsors , to valorize and maintain their financial support to IIGD. Also, the editor has proclaimed that all actions of IIGD are commanded and blessed by God, so, the faithful sponsor will be blessed while he or her has been connected to IIGD. The peculiarities of hybrid form of RGSF editorial is a study object of this master dissertation which aims to verify, through techniques of French Semiotics, how persuasive strategies are used by enunciator (or sender), how fiduciary contract is established between enunciator and enunciatee (or receiver or allocutor) and how ethos is built. As result of this investigation it could be established that editorial genre of religious journal is a hybrid form of genre of editorial, and it has been adapted to obtain high effective effects from persuasive strategies used by RGSF s editorial enunciator. It could also be verified that the conjunction of simple and hyperbolic language works very well to seduce and attract readers to enunciator s do-believe and do-do.